The effect of hyperstimulation on transforming growth factor b1 and b2 in the rat uterus: possible consequences for embryo implantation - Jovanovic, Aleksandra (My University, 2008)
Ovarian hyperstimulation is achieved through ovarian gonadotropin stimulation, and thus associated with supraphysiological levels of oestrogen and progesterone. To investigate the effects of exogenous gonadotropins on the expression of TGF b1 and TGF b2, which have been recognized as possible modulators of many endometrial functions, FSH and hCG were superimposed upon the normal hormonal milieu of the cycling rat, prior to mating. Endometrial tissue was collected at 4.5, 5.5 and 6.5 days after mating. ELISA was performed to estimate blood oestrogen and progesterone levels and immunohistochemistry was undertaken to localize TGF b1 and TGF b2 in the uterine endometrium. Apart from the known detrimental effects of hyperstimulation on gross morphology, hormone levels and endometrial histology, the hyperstimulation was also found to affect TGF b expression. An increase in the expression of TGF b2 was distinct in the glandular epithelium of the hyperstimulated animals, while regionalized expression of both TGF b1 and TGF b2 was prominent in the stroma. In conclusion, hyperstimulation affects the expression of both TGF b1 and TGF b2, which may contribute to the disruption of the endometrial environment required for successful embryo implantation.
Keywords: growth factor; rat uterus; embryo; implantation